Structure-Conduct-Performance (SCP) Analysis of Garut Sheep Market in Garut Regency - Nurhasanah, Sabrina; Firman, Achmad; Nurlina, Lilis (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
This study aims to analyze the structure, conduct, and performance (SCP) of the Garut sheep market in Garut Regency, West Java. Garut sheep are one of the region’s leading livestock commodities with high economic and cultural value. However, the marketing of Garut sheep remains inefficient due to issues such as imperfect market structures, price fluctuations, and the weak bargaining position of farmers. A descriptive quantitative research method was employed, utilizing a case study approach in six sub-districts of Garut Regency. Data were collected through surveys, interviews, observations, and focus group discussions (FGD) involving sheep farmers and market intermediaries. The findings indicate that the market structure for Garut sheep tends toward an oligopolistic model, characterized by a high level of concentration among large-scale traders. Market conduct is predominantly controlled by traders, particularly in price setting and transaction systems, while farmers act as price takers. Market performance is considered inefficient, as evidenced by high marketing margins and low farmer’s share. These results highlight the need for policy intervention to improve market structure and behavior, thereby enhancing marketing efficiency and farmer welfare.